Studies on the Effect of Polluted Water on Cassia auriculata Linn. Seeds. - SINGH., R.B. (Asian Journal of Chemistry, 2010)
Cassia auriculata Linn. seeds were treated with different distillery effluent concentrations. The catalase activity and chlorophyll contents were studied in 25%,50% and 100% of distillery effluent The catalase activity and chlorophyll contents were decreased in the seeds germination.